Chemokine (C‐C motif) receptor 2–positive monocytes aggravate the early phase of acetaminophen‐induced acute liver injury. Issue 5 (22nd July 2016) - Mossanen, Jana C.; Krenkel, Oliver; Ergen, Can; Govaere, Olivier; Liepelt, Anke; Puengel, Tobias; Heymann, Felix; Kalthoff, Sandra; Lefebvre, Eric; Eulberg, Dirk; Luedde, Tom; Marx, Gernot; et al.
Abstract : Acetaminophen (APAP, paracetamol) poisoning is a leading cause of acute liver failure (ALF) in humans and induces hepatocyte necrosis, followed by activation of the innate immune system, further aggravating liver injury. The role of infiltrating monocytes during the early phase of ALF is still ambiguous. Upon experimental APAP overdose in mice, monocyte‐derived macrophages (MoMFs) massively accumulated in injured liver within 12‐24 hours, whereas the number of tissue‐resident macrophages (Kupffer cells) decreased. Influx of MoMFs is dependent on the chemokine receptor, chemokine (C‐C motif) receptor 2 (CCR2), given that Ccr2 −/− mice display reduced infiltration of monocytes and attenuated liver injury post‐APAP overdose at early time points. As evidenced by intravital multiphoton microscopy of Ccr2 reporter mice, CCR2 + monocytes infiltrate liver as early as 8‐12 hours post‐APAP overdose and form dense cellular clusters around necrotic areas. CCR2 + MoMFs express a distinct pattern of inflammatory, but also repair‐associated, genes in injured livers. Adoptive transfer experiments revealed that MoMFs primarily exert proinflammatory functions early post‐APAP, thereby aggravating liver injury. Consequently, early pharmacological inhibition of either chemokine (C‐C motif) ligand (CCL2; by the inhibitor, mNOX‐E36) or CCR2 (by the orally available dual CCR2/CCR5 inhibitor, cenicriviroc) reduces monocyte infiltration and APAP‐induced liver injury (AILI) in mice. Importantly, neither the early nor continuous inhibition of CCR2 hinder repair processes during resolution from injury. In line with this, human livers of ALF patients requiring liver transplantation reveal increased CD68 + hepatic macrophage numbers with massive infiltrates of periportal CCR2 + macrophages that display a proinflammatory polarization. Conclusion : Infiltrating monocyte‐derived macrophages aggravate APAP hepatotoxicity, and the pharmacological inhibition of either CCL2 or CCR2 might bear therapeutic potential by reducing the inflammatory reaction during the early phase of AILI. (Hepatology 2016;64:1667‐1682)